Front Cover: Time‐Efficient Object Recognition in Quantum Ghost Imaging (Adv. Quantum Technol. 2/2023). Issue 2 (9th February 2023) - Moodley, Chané; Ruget, Alice; Leach, Jonathan; Forbes, Andrew
Abstract : The cover illustrates the birth of entangled photons used in quantum ghost imaging. The idler photons interact with the object while the signal photons are spatially resolved. Machine learning (ML) is employed to speed up the quantum imaging process. The nodal sphere is representative of ML while the 0 s and 1 s represent early recognition by logistic regression. Logistic regression demonstrates a 10x speed up in image acquisition time with a 99% prediction accuracy. More details can be found in article number 2200109 by Chané Moodley and co‐workers.